Study guides

☆☆

Q: X2 plus 6x plus 9 equals 49?

Write your answer...

Submit

Still have questions?

Related questions

The quadratic expression x2+6x+8 when factorised equals (x+2)(x+4)

x2 + 6x + 9 = 81 x2 + 6x = 72 x2 + 6x - 72 = 0 (x+12)(x-6) = 0 x= -12, 6 (two solutions)

-x2+14x=49

x2 + 49 = 0 ∴ x2 = -49 ∴ x = 7i

x2 + 6x + 12 = 0 x2 + 6x + 9 = -3 (x + 3)2 = -3 x + 3 = ± √-3 x = -3 ± i√3

one

(3, -21)

y â‰¥ 11

7

x2 + 6x - 2 = 0 x2 + 6x + 9 = 13 (x + 3)2 = 13 x + 3 = ± √13 x = -3 ± √13

y = x2 - 6x + 2 y = x2 - 6x + 9 - 7 y = (x - 3)2 - 7

(x-5)(x+11)

x2 + 6x = x*(x + 6)

2x+6x=-9 => 8x=-9=> x=-8/9

x2 + 6x + 8 = 0 Solve for x.X = -2 or X = -4

A quadratic equation. If you wish to solve for x, you can do so as follows: -x2 + 6x + 7 = 0 x2 - 6x - 7 = 0 (x - 7)(x + 1) = 0 x ∈ {-1, 7}

-x2 + 6x + 16 = -(x2 - 6x - 16) = -(x - 8)(x + 2) = -(8 - x)(x + 2)

x2+6x-40 = 0 (x+10)(x-4) = 0 x = 4 or x = -10

x2 + 6x - 110 = 0 ∴ x2 + 6x = 110 ∴ x2 + 6x + 36 = 146 ∴ (x + 6)2 = 146 ∴ x + 6 = ±1461/2 ∴ x = -6 ±1461/2 ∴ x ≈ 6.083, 18.083

x2 + 6x = 7 ⇒ x2 + 6x + 9 = 7 + 9 ⇒ (x + 3)2 = 16 ⇒ x + 3 = ±4 ⇒ x = -7 or 1

Yes

x2 + 6x + 8 = (x + 4)(x + 2)

x3 + x2 - 6x + 4 = (x - 1)(x2 + 2x - 4)

(x - 3)(x - 2)

x = -3y = -14